2014
DOI: 10.1186/1746-4269-10-46
|View full text |Cite
|
Sign up to set email alerts
|

Use and management of traditional medicinal plants by Maale and Ari ethnic communities in southern Ethiopia

Abstract: BackgroundAround 80% of the people of Ethiopia are estimated to be relying on medicinal plants for the treatment of different types of human health problems. The purpose of this study was to describe and analyse the use and management of medicinal plants used for the treatment of human health problems by the Maale and Ari communities in southern Ethiopia.MethodsQuantitative and qualitative ethnobotanical field inquiries and analytical methods including individual and focus group discussions (18), observations,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
74
0
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 98 publications
(82 citation statements)
references
References 11 publications
6
74
0
2
Order By: Relevance
“…That is, according to the category of uses, the pattern of plant knowledge might vary among the social groups. On the second hand, most studies have come up with a positive association between age and traditional knowledge (Case et al 2005, Kidane et al 2014, Saynes-Vásquez et al 2013, probably because knowledge tends to accumulate through life cycle (Beltrán-Rodríguez et al 2014). But, it is worth understanding whether this trend varies according to the type of occupation.…”
Section: Ethnobotany Research and Applications 232mentioning
confidence: 99%
“…That is, according to the category of uses, the pattern of plant knowledge might vary among the social groups. On the second hand, most studies have come up with a positive association between age and traditional knowledge (Case et al 2005, Kidane et al 2014, Saynes-Vásquez et al 2013, probably because knowledge tends to accumulate through life cycle (Beltrán-Rodríguez et al 2014). But, it is worth understanding whether this trend varies according to the type of occupation.…”
Section: Ethnobotany Research and Applications 232mentioning
confidence: 99%
“…This study provides evidence that the yellow baboon forages for similar plants also used in ethno medicine as seen from previous literature reviewed [16,17,22,23]. 27.5% of microbes that affect nonhuman primates affect humans as well, Staphylococcus aureus, Salmonella, and Escherichia coli being only a few examples of such microbes, a factor attributed to our phylogenetic closeness [4,12,36,37].…”
Section: Discussionmentioning
confidence: 70%
“…Sterculia africana root is used to treat asthma in communities around Lake Victoria region in Tanzania [21] and also possesses strong antifungal activity [18]. The Maale and Ari communities in Ethiopia utilize Sterculia africana as an antiemetic and to treat food poisoning as well as treating fever in the Blue Nile state, Sudan [22,23]. Sterculia africana is one of the sources of nontraditional seed oils in Botswana [24] and is widely used in African traditional medicine.…”
Section: Introductionmentioning
confidence: 99%
“…Some studies have shown the antifertility/spermicidal potentials of some medicinal plants (Huffman, 2003;Khillare and Singh, 2014). Fertility regulating plants and plant products have been traditionally used to control birth in different parts of Africa (Kidane et al, 2014). Leptadenia hastata Pers Decne (Njara in Kanuri, Yadiya in Hausa, Sabato, Kusubi in Fulani and Hagalhadjar in Arabic) belongs to the family Asclepiadaceae (Thomas, 2012).…”
Section: Introductionmentioning
confidence: 99%